Mechanisms by Which Liposomes Improve Inhaled Drug Delivery for Alveolar Diseases. Issue 3 (10th March 2023) - Ferguson, Laura T.; Ma, Xiaonan; Myerson, Jacob W.; Wu, Jichuan; Glassman, Patrick M.; Zamora, Marco E.; Hood, Elizabeth D.; Zaleski, Michael; Shen, Mengwen; Essien, Eno-Obong; Shuvaev, Vladimir V.; Brenner, Jacob S.
Abstract : Nanomedicine Drug‐filled lipid nanocarriers are inhaled for deposition in the alveoli, spherical sacs that are the functional unit of the lung. In article number 2200106, Jacob S. Brenner and co‐workers demonstrate that inhaled liposomes are stable in surfactant, avoid intra‐alveolar macrophages, prolong drug half‐life, and increase total drug delivered to the lung.